(untitled) (Research, Society and Development, 2020)
The objective of the study was to evaluate the effect of inclusion of enzyme complex in diets of corn and soybean meal upon the metabolizable energy, heat production, zootechnical performance, intestinal morphometry, carcass yield and commercial cuts of broilers, in the period of 21 to 42 days. Metabolism and performance test were performed in a completely randomized design with 4 treatments (Positive Control (CP) and Negative Control (CN), with enzyme complex and without enzyme complex, respectively), 8 repetitions of 4 birds (metabolism) and 15 birds (performance)). Metabolizable energy, heat production, intestinal histomorphometry, zootechnical performance, carcass yield and economic evaluation were analyzed. No effects were observed for metabolizable energy and heat production when enzymes to the diets were added. There was no effect of the treatments upon the performance and the carcass yield. The enzymes caused an increase in the width of the crypt in the duodenum. The others variables (villus height and width, crypt height, wall thickness) of the duodenum, jejunum and ileum were not influenced. Enzymes in diets without energy reduction are not economically viable in the period of 21 to 42 days of age.